HYBRID SHOPPING MODELS: WHERE INNOVATION MEETS TRADITION IN THE MODERN MALL - Ikram Saidi,; Feyrouz Ahlam Saidi, (International Journal of Innovative Technologies in Social Science, 2025)
This study investigates the pivotal role of innovation in shopping malls, which is integral to their success within the competitive retail environment. As consumer expectations evolve, malls must transcend conventional models by incorporating sustainability, advanced technologies, and personalized experiences. The research focuses on these dynamics through fieldwork and visitor surveys conducted at Retaj and Yes Malls in Ali Mendjeli City, Algeria. A comprehensive analytical framework evaluates dimensions such as multifunctionality, sustainability, technological integration, and community engagement. Employing a mixed-methods approach with 100 valid questionnaires, the study examines visitor preferences, particularly in the post-COVID-19 context. The findings underscore visitors' emphasis on eco-friendly features and highlight the multifunctional nature of malls as spaces for shopping, entertainment, services, and social interaction, supported by rigorous chi-square analysis. Technological innovations are classified into two categories: enhancing the shopping experience and fostering customer engagement, with a particular focus on entertainment that reflects local cultural contexts. Accessibility emerges as a key factor, with proximity to public transportation significantly increasing mall attractiveness. While respondents value technological advancements, they prefer a hybrid approach that combines augmented reality (AR) and artificial intelligence (AI) with traditional in-person shopping experiences. This equilibrium sustains malls' roles as social hubs, ensuring community engagement while embracing modern innovation.